Framing and feedback in social dilemmas with partners and strangers - Caleb A. Cox; Brock Stoddard (Games, 2015)
We study framing effects in repeated social dilemmas by comparing payoff-equivalent Give- and Take-framed public goods games under varying matching mechanisms (Partners or Strangers) and levels of feedback (Aggregate or Individual). In the Give-framed game, players contribute to a public good, while in the Take-framed game, players take from an existing public good. The results show Take framing and Individual-level feedback lead to more extreme behavior (free-riding and full cooperation), especially for Partners. These results suggest Take framing and Individual-level feedback increase the variability of cooperation.
Keywords: C72; C73; C92; H41; 330; public goods; experiment; framing; cooperation